Modele wyborów dyskretnych i ich estymacja w programie R - Bąk, Andrzej (Discrete Choice Models and their Estimation in R Computer Programme, 2009)
The aim of the paper is to present discrete choice models estimation procedure using R computer programme function and own function wrote in R computer language. The paper presents: basic description of conditional logit model, packages and procedures available in R computer programme that are useful in discrete choice methods, own functions wrote in R computer language that are useful in some computing tasks not supported yet in standard R packages, the example of application R functions in estimation of discrete choice model. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 50-60